2021
DOI: 10.1155/2021/7955791
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of TRPV1 on Oxidative Stress-Induced Autophagy and Apoptosis in Microglia

Abstract: Stroke mostly including ischemic stroke is the second leading mortality and disability worldwide. Oxidative stress injury occurred during ischemic stroke treatment generally. A high amount of reactive oxygen species (ROS) is involved in oxidative stress induction. Transient receptor potential vanilloid 1 (TRPV1) has been shown to regulate oxidative stress and apoptosis in microglia; however, the detailed mechanisms remain unclear. We aimed to explore whether autophagy-regulated oxidative stress and apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…TRPV1 is directly related to oxidative stress in many studies including hippocampus, pain, ischemia-reperfusion, and brain damage [45,46]. We can explain the suppression of oxidative damage in capsaicin groups with TRPV1, which emerged in the study of TRPV1 of capsaicin.…”
Section: Discussionmentioning
confidence: 85%
“…TRPV1 is directly related to oxidative stress in many studies including hippocampus, pain, ischemia-reperfusion, and brain damage [45,46]. We can explain the suppression of oxidative damage in capsaicin groups with TRPV1, which emerged in the study of TRPV1 of capsaicin.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, an in vitro OGD/reoxygenation (OGD/R) model has been established to induce cerebral I/R injury. In the in vitro OGD/R microglial model, TRPV1 could partly activate OGD/R‐induced microglial autophagy, which impedes oxidative stress‐induced injury and apoptosis (Huang et al., 2021 ; Lin et al., 2022 ). Based on the previous result, 6‐gingerol treatment, which possesses anti‐apoptotic and anti‐inflammatory effects, was employed and was shown to significantly attenuate cerebral infarct volume, improve brain edema and neurological scores, and reverse brain histomorphological damage after I/R injury (Luo et al., 2021 ).…”
Section: Trpv Channelsmentioning
confidence: 99%
“…Huang et al found that primary microglia produced large amounts of reactive oxygen species (ROS) due to oxidative stress in OGD/R injury. Additionally, they revealed that enhanced autophagy could reduce the level of ROS and reduce oxidative stress-related apoptosis ( Huang T. et al, 2021 ), whereas Chen et al (2016) found that inhibition of autophagy could reduce microglial apoptosis/death in OGD/R injury in BV2 microglia. Yang et al (2014c) also demonstrated that autophagy promoted hypoxia-induced cell death in primary microglia.…”
Section: Interaction Between Microglial Autophagy and Other Biologica...mentioning
confidence: 99%